Staff awards '96 - De La Salle University, Manila (Animo Repository, 1996)
The University honored its 25 loyal employees during the Staff Awards '96. The theme of this year's awards is Kawaning Lasalyano: Bukas ang Kaisipan at Damdamin Tungo sa Pangangailangan ng Lumalaking Multibersidad.